2021
DOI: 10.1161/hypertensionaha.120.16217
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Pressure During the Development of Renovascular Hypertension

Abstract: The mechanisms by which changes in intracranial pressure (ICP) occur during hypertension are unclear. The experimental 2K1C (2-kidney, 1-clip) hypertension is a model characterized by sympathetic and renin-angiotensin system overactivation in which ICP still needs investigation. In the present study, we analyzed ICP alterations during the development of 2K1C hypertension using invasive and noninvasive ICP recording methods. We also tested the importance of AT1R (angiotensin II type 1 receptor) activation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The B4C device does not provide ICP values; however, it allows a bedside observation and report of the ICP pulse waveform quantitative parameters, a vital sign that is gaining attention in recent years [36,37]. Studies evaluating this ICC device in critically ill patients are few and still ongoing [38]; nevertheless, ICC was adequately assessed in children with hydrocephalus [21] and in experimental studies using this technique [39]. Together with TCD-derived variables, a combination of cerebral hemodynamics and intracranial compliance assessment could provide interesting information about brain function in different critically ill patients [20]; in particular, in our study, we observed that only the CVH/ICC score was significantly different between FO and UO patients, which may suggest that the combination of these parameters, rather than a single one, could be more sensitive and a better predictor for patients' outcome in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The B4C device does not provide ICP values; however, it allows a bedside observation and report of the ICP pulse waveform quantitative parameters, a vital sign that is gaining attention in recent years [36,37]. Studies evaluating this ICC device in critically ill patients are few and still ongoing [38]; nevertheless, ICC was adequately assessed in children with hydrocephalus [21] and in experimental studies using this technique [39]. Together with TCD-derived variables, a combination of cerebral hemodynamics and intracranial compliance assessment could provide interesting information about brain function in different critically ill patients [20]; in particular, in our study, we observed that only the CVH/ICC score was significantly different between FO and UO patients, which may suggest that the combination of these parameters, rather than a single one, could be more sensitive and a better predictor for patients' outcome in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In opposition to what was believed, a previous publication in animal models revealed an increase in intracranial pressure just a few weeks after inducing renovascular hypertension, meaning that this injury begins in the early phases of BP elevation. The observed results in hypertensive rats and in patients with essential hypertension suggests that several concepts regarding cerebral autoregulation should be revisited (10,21).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, in 2021, Fernandes et al (10) reported that after three weeks of induced renovascular hypertension in a rat model, there was a deleterious effect on ICP dynamics compatible with intracranial hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental and non-original papers, most of these articles were piloting the use of the device in patients with various neurological and non-neurological conditions. These included cryptococcal meningitis [5], renovascular hypertension [26], pediatric hydrocephalus [2], obesity [8], critical COVID-19 [10], end-stage renal disease [41], pregnancy [19], patients sedated for gastrointestinal endoscopy [24], sedentary chronic stroke patients [40], hemodialysis patients [42], prostatectomy surgery patients [45], fibromyalgia [33], cardiovascular surgery patients [1], diabetes and chronic kidney disease [35], and migraine [14]. To the best of our knowledge, this is the first prospective study to compare the Brain4Care noninvasive method with the invasive gold standard in TBI.…”
Section: Discussionmentioning
confidence: 99%